Following a Long-Distance Classical Race the Whole-Body Kinematics of Double Poling by Elite Cross-Country Skiers Are Altered - Zoppirolli, Chiara; Bortolan, Lorenzo; Stella, Federico; Boccia, Gennaro; Holmberg, Hans-Christer; Schena, Federico; Pellegrini, Barbara (Frontiers in Physiology, 2018)
Introduction: Although short-term (approximately 10-min) fatiguing DP has been reported not to alter the joint kinematics or displacement of the CoM of high-level skiers, we hypothesize that prolonged DP does change these kinematics, since muscular strength is impaired following endurance events lasting longer than two hours. Methods: During the 58-km Marcialonga race in 2017, the fastest 15 male skiers were videofilmed (100 fps, FHD resolution in the sagittal plane) on two 20-m sections (inclines: 0.7 ± 0.1°) 48 km apart (i.e., 7 and 55 km from the start), approximating 50- km Olympic races. The cameras were positioned perpendicular to and about 40 m from the middle of each section and spatial dimensions adjusted for each individual track skied. Pole and joint kinematics, as well as displacement of the CoM during two DP cycles were assessed. Results: The 10 skiers who fulfilled our inclusion criteria finished the race in 2 h 09 min 19 s ± 28 s. Displacements of the joints and CoM were comparable to previous observations OF skiers roller skiing on a flat treadmill at similar speeds in the laboratory. 55 km after the start, cycle velocity and length were lower (P<0.001 and P=0.002, respectively) and the angular range of elbow joint flexion during the initial part of the poling phase reduced, while shoulder angle was greater during the first 35% of the DP cycle (all P<0.05). Moreover, the ankle angle was increased and forward displacement of the CoM reduced during the first 80% of the cycle. Conclusions: Prolonged DP reduced the forward displacement of the CoM and altered arm kinematics during the early poling phase. The inefficient utilization of CoM observed after two hours of competition together with potential impairment of the stretch-shortening of arm extensor muscles probably attenuated generation of poling force. To minimize these effects of fatigue, elite skiers should focus on maintaining optimal elbow and ankle kinematics and an effective forward lean during the propulsive phase of DP.